2020
DOI: 10.22270/jddt.v10i5-s.4537
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and antioxidant activity of ethanolic extracts from Citrus sinensis L. and Citrus reticulata L. fruits

Abstract: Citrus fruits, in particular the genus Citrus, are very rich in antioxidants which have beneficial effects on human health. The objective of this study was to evaluate the phenolic content and the antioxidant activity of the ethanolic extracts from orange (Citrus sinensis L.) and mandarin (Citrus reticulata L.) fruits. The quantitative estimation of the total phenolic content in the two extracts revealed their richness in these compounds. The results obtained showed that the polyphenols content were 159.66 ± 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In the citrus × clementina pulp extracts, the total antioxidant capacity (TAC) was found to be three-fold higher (7.1 mmol TE/mg fresh weight [FW]) compared to Citrus reticulata (2.6 mmol TE/mg FW) and six-fold higher compared to Citrus japonica (1.2 mmol TE/mg FW). Similarly, Citrus sinensis and Citrus reticulata fruits possessed good antioxidant activity studied by the hydroxyl radical scavenging activity and reducing power capacity methods (Bentahar et al, 2020). Fratianni et al (2019) indicated that Citrus bergamia and Citrus medica cv.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…In the citrus × clementina pulp extracts, the total antioxidant capacity (TAC) was found to be three-fold higher (7.1 mmol TE/mg fresh weight [FW]) compared to Citrus reticulata (2.6 mmol TE/mg FW) and six-fold higher compared to Citrus japonica (1.2 mmol TE/mg FW). Similarly, Citrus sinensis and Citrus reticulata fruits possessed good antioxidant activity studied by the hydroxyl radical scavenging activity and reducing power capacity methods (Bentahar et al, 2020). Fratianni et al (2019) indicated that Citrus bergamia and Citrus medica cv.…”
Section: Antioxidant Potentialmentioning
confidence: 99%
“…In addition, luteolin, Apigenin, Genkwanin were found for the species Rosmarinus officinalis L. and diosmetin, naringin, tangeretin, quercetin, nobiletin and narirutin for Citrus × sinensis . Phenolic acids were found in two species, Gallic acid, Caffeic acid, Ferulic acid, Coumaric acid, caffeic acid, found in in higher concentrations in Citrus × sinensis and, naturally, rosmarinic acid (only present in Rosmarinus officinalis L. species), found in higher concentrations in the other species mentioned [ 61 , 62 , 63 ]. Typical phenolics with antioxidant activity are primarily flavonoids (as we have mentioned) and phenolic acids.…”
Section: Resultsmentioning
confidence: 99%
“…Although hesperidin is the major flavonoid in both species, it is found in higher concentrations in the species Rosmarinus officinalis L. than in Citrus × sinensis , which has more types of flavonoids; therefore, the concentrations are more dispersed. This may be a possible justification for the small difference in IC 50 [ 61 , 62 , 63 ]. Furthermore, an important difference between these two compounds is the presence of rosmarinic acid in only one of the species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nutritional benefits of citrus fruit consumption on human health are well demonstrated (Campone et al, 2020). C. sinensis has been used in traditional medicine to treat medical conditions such as constipation, cramps, colic, diarrhea, bronchitis, tuberculosis, cough, cold, menstrual disorder, angina, hypertension, anxiety, depression and stress (Favela-Hernández et al, 2016;Bentahar et al, 2020). In addition, these fruits are used also to treat bowel disorders, respiratory disorders, cardiovascular disease, and stress (Mannucci et al, 2018).…”
Section: Introductionmentioning
confidence: 99%